ELECTRIC FIELD HOMOGENEITY PROBLEM IN THE MULTI-ELECTRODE PHASE-ADJUSTABLE APPLICATOR - Zinkovskiy, Yu. F.; Sydoruk, Yu. K.; Turovskiy, A. O. (Radio Electronics, Computer Science, Control, 2014)
In our study we have proposed a mathematical model of multiphase cylindrical apparatus for bulk materials treatment with radio frequency electric field. According to the model the analysis of the distribution of the electric field inside the zone restricted with multiple connected circular arc-shaped boundary on the basis of the field coupling problem of the theory of singular integral equations is performed. The expressions for determination of the electric field strength in the core are given. Also we propose a schematic diagram of the generator for the electrodes excitation and the principle of building of the apparatus for treatment of grain and other bulk materials with the electric field of radio frequency.